Dark side of the tune [ popular music and violence - Johnson, Bruce , 1943-; Cloonan, Martin (Ashgate popular and folk music series, 2009)
This book focuses on the 'dark side' of popular music by examining the ways in which popular music has been deployed in association with violence. Cloonan and Johnson address the physiological and cognitive foundations of sounding/hearing and provide a historical survey of examples of the nexus between music and violence, from (pre)Biblical times to the late nineteenth century. The book also concentrates on the emergence of technologies by which music can be electronically augmented, generated, and disseminated. The authors investigate the implications of this nexus both for popular music stud.